Evaluation of clinical outcome post lower limb angioplasty in peripheral arterial disease patient - Chin, Leong Yung (2017)
Introduction Peripheral arterial disease is caused by atherosclerosis or thromboembolic processes that alter the structure and function of the arteries of the lower extremity. Most of the patients presented to medical personnel after they experience claudication, non-healing wound, or foot gangrene which increases the risk of amputation. The aim of treatment in PAD with its complication is to maintain the vascular patency and preserve a functional limb. Lower limb angioplasty service was started since year 2012 in this centre and referral were received from various unit in this facility (vascular, orthopaedics, plastic etc.) and other nearer health centers. The purpose of this study was to evaluate the safety and efficacy of lower limb angioplasty procedure in term of lower limb salvage. Objective The main objective of this study was to evaluate the safety and efficacy of lower limb angioplasty in treating peripheral arterial disease patients at intervals of 6months and 1-year interval. Clinical outcome was based on successful limb salvage where patients able to preserve talus and calcaneus after amputation at the Chopart level or distal to it. In addition, this study will help to identify the factors for successful limb salvage. Methods 35 patients (37 lower limbs) aged between 40 to 82 years old who had been treated with lower limb angioplasty for peripheral arterial disease were selected from Advanced Minimally Invasive Endovascular and Neurointerventional (AMIEN) Unit registry in Hospital Universiti Sains Malaysia. The patients were identified according to the pre-determined inclusion and exclusion criteria by using Hospital PACS system. All lower limb angioplasty was performed by an interventional radiologist and the angiogram result prior to angioplasty was validated. Angiogram films were studied when the data provided in the previous report were insufficient. 6 months and 1-year clinical outcome of angioplasty was accessed by tracing the patient folder. The data were diligently collected and were analysed using the IBM® Social Science and Statistical Packaged (SPSS) software. Results and conclusion The technical success rate for lower limb angioplasty in this centre was 89%, however, the limb salvage rate at 6 months and 12 months was only 67.5%. This study had shown that the technical success of lower limb angioplasty does not equal to successful limb salvage. Lower limb angioplasty was considered a safe and efficient procedure with minimal complication and low technical failure rate. The study failed to demonstrate the factors that influence the clinical outcome of lower limb angioplasty. An extensive study involving larger samples from various regions in the country is recommended for a more conclusive and representative data for our Malaysian populations.